2018
DOI: 10.1177/2325967118791754
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Findings of Soccer Injuries During the 2017 Gold Cup

Abstract: Background:Surveillance programs are vital to analyze the cause and nature of lesions and ultimately establish protocols of action to lower injury rates.Purpose:To evaluate the adherence of team doctors to an electronic surveillance system and determine the incidence and characteristics of injuries among soccer players participating in the 2017 Gold Cup.Study Design:Descriptive epidemiological study.Methods:All data were collected from the electronic medical reports submitted during each match of the 2017 Gold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 12 publications
(28 reference statements)
1
11
0
Order By: Relevance
“…Knee injuries represent 17% (7%–23%) of all injuries in male youth players ( 32 ). In addition, one-third are reported to be due to poor knee function and to occur without contact ( 36 , 37 ). It has previously been shown that 10–15 min of neuromuscular training 2–3 times weekly reduces non-contact injuries by 45% in youth football players ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Knee injuries represent 17% (7%–23%) of all injuries in male youth players ( 32 ). In addition, one-third are reported to be due to poor knee function and to occur without contact ( 36 , 37 ). It has previously been shown that 10–15 min of neuromuscular training 2–3 times weekly reduces non-contact injuries by 45% in youth football players ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge that certain playing situations have a potential to cause HAEs of greater magnitudes (eg, marking contest) among specific players (eg, female players) can inform match and player development with regard to coaching drills, individual skills training, and rule revision as required. In contact sports, increasing rates of injuries that become apparent as the match progresses 16,29,33 might be reduced by instituting the more frequent interchange rotation of novice players, thereby mitigating exposure to head impacts and possible injury.…”
Section: Discussionmentioning
confidence: 99%
“…2 Soccer accounts for 228,000 injuries per year in the United States alone and results in a worldwide cost of over $30 billion. 3 Soccer is a contact sport with frequent changes of direction, often played at maximum intensity, which poses a risk of injury. The number of injuries is highest in adolescents.…”
Section: Introductionmentioning
confidence: 99%
“… 2 Soccer accounts for 228,000 injuries per year in the United States alone and results in a worldwide cost of over $30 billion. 3 …”
Section: Introductionmentioning
confidence: 99%